Specific chromosome aberrations in ataxia telangiectasia. - Oxford, J M (1975)
Cytogenetic observations on seven cases of ataxia telangiectasia are presented. The aberration frequency was found to be increased in all of them with a specificity for the involvement of the D-group chromosomes in rearrangements. Clones of cytogenetically abnormal cells were observed in the lymphocytes of three cases and in the cultured skin fibroblasts of two cases, again with a specificity for D-group involvement. G-banding shows that chromosome 14 is frequently involved in rearrangements in clone cells and that the band 14q12 may be a highly specific exchange point. The significance of lymphocyte clones with a proliferative advantage in vivo is discussed. Cytogenetic studies of the parents and sibs of these cases are also reported.